2010
DOI: 10.1007/s10689-010-9323-z
|View full text |Cite
|
Sign up to set email alerts
|

Carney triad versus Carney Stratakis syndrome: two cases which illustrate the difficulty in distinguishing between these conditions in individual patients

Abstract: Carney triad is a usually sporadic association of pulmonary chondroma, gastrointestinal stromal tumours, and paraganglioma. The majority of patients have two of these tumours, the gastric and pulmonary tumours being the most common combination. Carney Stratakis syndrome is an association of familial paraganglioma and gastric stromal sarcoma and it is considered to be a distinct condition from Carney triad as it is dominantly inherited and not associated with pulmonary chondroma. We report two unrelated patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…It is an autosomal dominantly inherited dyad of familial paraganglioma and gastric stromal sarcoma (no pulmonary lesion) with germline mutations in SHD subunits B, C and D. Our report demonstrates the difficulties in distinguishing incomplete Carney triad and Carney-Stratakis syndrome, as also recognised by others [6].…”
Section: Discussionsupporting
confidence: 56%
“…It is an autosomal dominantly inherited dyad of familial paraganglioma and gastric stromal sarcoma (no pulmonary lesion) with germline mutations in SHD subunits B, C and D. Our report demonstrates the difficulties in distinguishing incomplete Carney triad and Carney-Stratakis syndrome, as also recognised by others [6].…”
Section: Discussionsupporting
confidence: 56%
“…22 The combination of NB, PGL and renal cell carcinoma was first described by Fairchild et al 23 Most recently, the case of a patient who was found to have at the same time malignant NB, PHEO and renal cell carcinoma was described; sequence analysis revealed an SDHB mutation. 24 In another patient with NB and a PGL, a germline SDHB gene deletion was found.…”
Section: Discussionmentioning
confidence: 97%
“…Germline mutations of SDH, as seen in CSS, result in autosomal dominant inherited cancer syndromes with variable clinical presentations and metastatic potential [13] . Therefore, genetic testing provides a definitive diagnosis of CSS and should be utilized for early detection of the syndrome in immediate family members and descendants [1 , 5 , 14] .…”
Section: Discussionmentioning
confidence: 99%